Forest site classification of forest ecosystems in Bohemian Karst (Czech Republic) - P. Šamonil; J. Viewegh (Journal of Forest Science, 2005)
The study focuses on selected forest site units on water uninfluenced sites on limestone in Bohemian Karst. The species composition of phytocoenoses, their potential production and soil properties were assessed. Studied forest site complexes are correctly determined and they provide important information from the aspect of planning and practical nature conservation management. It is necessary to specify the criteria of categoria calcaria in detail, since it is often difficult to distinguish it from categoria mesotrophica. Water retention capacity of soils, a criterion often neglected so far, presents a useful view of forest site water budget and it is a suitable criterion in forest site classification.